A case report of Grover's disease from immunotherapy-a skin toxicity induced by inhibition of CTLA-4 but not PD-1. Issue 1 (December 2016) - Uemura, Marc; Faˈak, Faisal; Haymaker, Cara; McQuail, Natalie; Sirmans, Elizabeth; Hudgens, Courtney; Barbara, Lydia; Bernatchez, Chantale; Curry, Jonathan; Hwu, Patrick; Tetzlaff, Michael; Diab, Adi
Abstract Background Immune related adverse events (irAEs) are common side effects of checkpoint inhibitory (CPI) therapies targeting CTLA-4 and PD-1/PD-L1. Grover's disease is an uncommon dermatologic condition with unclear pathogenesis previously reported as an irAE with ipilimumab. Case Presentation We report an additional case of ipilimumab-induced Grover's disease. Interestingly, this dermatologic side effect did not appear with use of anti-PD-1 therapy in our patient. Immune analysis was performed and suggests a possible role of Th2 cells in its patholgenesis. Conclusion This case suggests that Grover's disease is an irAE induced by Ipilimumab. Our immune analysis suggests that Th2 cells may be pathogenic mediators which warrants further study.